Automatic calving front delienation on TerraSAR-X and Sentinel-1 SAR imagery - Krieger, Lukas; Floricioiu, Dana (2017)
This paper presents an approach for automatic calving front delineation of marine-terminating outlet glaciers. We utilize a Canny edge detection approach together with a shortest path optimization problem to find calving front locations (CFL) on SAR backscattering images from Sentinel-1 and TerraSARX. The CFLs are detected on Stripmap images acquired over Zachariae Isstroem in Northeast Greenland where difficult conditions for CFL retrieval exist. We compare our results to CFLs that are delineated by hand and find good agreement, independent of the used sensor.